The CaSR in Pathogenesis of Breast Cancer: A New Target for Early Stage Bone Metastases - Das, Souvik; Clézardin, Philippe; Kamel, Said; Brazier, Michel; Mentaverri, Romuald (Frontiers in Oncology, 2020)
The Ca2+-sensing receptor (CaSR) is a class-C G protein-coupled receptor which plays a pivotal role in calciotropic processes, primarily in regulating parathyroid hormone secretion to maintain systemic calcium homeostasis. Among its non-calciotropic roles, where the CaSR sits at the intersection of myriad processes, it has steadily garnered attention as an oncogene or tumor suppressor in different organs. In maternal breast tissues the CaSR promotes lactation but in breast cancer it acts as an oncoprotein and has been shown to drive the pathogenesis of skeletal metastases from breast cancer. Even though research has made great strides in treating primary breast cancer, there is an unmet need when it comes to treatment of metastatic breast cancer. This review focuses on how the CaSR leads to the pathogenesis of breast cancer by contrasting its role in healthy tissues and tumorigenesis, and by drawing brief parallels with the tissues where it has been implicated as an oncogene. A class of compounds called calcilytics, which are CaSR antagonists, have also been surveyed in the instances where they have been used to target the receptor in cancerous tissues and constitute a proof of principle for repurposing them. Current clinical therapies for treating bone metastases from breast cancer are limited to targeting osteoclasts and a deeper understanding of the CaSR signaling nexus in this context can bolster them or lead to novel therapeutic interventions.